Three-Dimensional Imaging of a Central Venous Dialysis Catheter Related Infected Thrombus - Diana Yuan Yng Chiu; Darren Green; Philip A. Kalra; Nik Abidin (Case Reports in Nephrology)
Three-dimensional (3D) echocardiography is becoming widely available and with novel applications. We report an interesting case of a 68-year-old lady with a central venous thrombosis coincident with both a dialysis catheter infection and a recent pacemaker insertion. Two-dimensional transesophageal echocardiography was unable to delineate whether the thrombosis was involved with the pacemaker wire or due to the tunneled catheter infection. The use of 3D echocardiography was able to produce distinct images aiding diagnosis. This circumvented the need for invasive investigations and inappropriate, high-risk removal of the pacing wire. This case highlights the emerging application of 3D echocardiography in routine nephrology practice.